2006
DOI: 10.1177/0961463x06066944
|View full text |Cite
|
Sign up to set email alerts
|

The Persistence of the Standardized Life Cycle

Abstract: This article investigates to what degree the standardized life cycle has been replaced by an individualized life course, characterized by the absence of a strict sequence and timing of life's transitions. In order to measure the normative position of people, rather than the external conditions to which they are subject, the test is based on the ideal life course or life cycle as described by a purely random sample of 4666 inhabitants of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
0
8

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(64 citation statements)
references
References 11 publications
2
52
0
8
Order By: Relevance
“…This is a simple but important statement that, at least with regard to the sequence of the first events in each of the important careers (professional, residential, conjugal and parental), illustrates the 'persistence of the standardized life cycle' (Elchardus and Smits: 2006). This persistence is much more evident in the 'lived' (Billari, 2005) lives rather than the 'experienced' (Billari, 2005) ones which were already analysed previously.…”
Section: 12mentioning
confidence: 98%
“…This is a simple but important statement that, at least with regard to the sequence of the first events in each of the important careers (professional, residential, conjugal and parental), illustrates the 'persistence of the standardized life cycle' (Elchardus and Smits: 2006). This persistence is much more evident in the 'lived' (Billari, 2005) lives rather than the 'experienced' (Billari, 2005) ones which were already analysed previously.…”
Section: 12mentioning
confidence: 98%
“…It has been argued that these processes have increased diversity in demographic family behavior between individuals, which has been referred to as destandardization of the life course. While some studies have found support for this idea (Elzinga and Liefbroer 2007;Widmer and Ritschard 2009), there is also empirical evidence showing a fairly strong consensus concerning the timing and sequencing of important life transitions among young adults from recent birth cohorts (Elchardus and Smits 2006;Nico 2014). In other words, while the transition to adulthood has without doubt become more lengthy and complex for youth in Western societies, the extent to which these developments have actually increased diversity in family behavior between individuals remains a topic of controversy in the literature.…”
Section: Destandardization Of the Life Coursementioning
confidence: 98%
“…Dar prieš kelis dešimtmečius perėjimas iš paauglystės į socialinę brandą buvo siejamas su atitinkamais riboženkliais, t. y. mokyklos baigimas, išėjimas iš tėvų namų, nuolatinio darbo susiradimas, santuoka, pirmo vaiko gimimas (Hutchison 2008;Elchardus, Smits 2006) ir t. t. Jaunas žmogus gaudavo dirbančio, vedusio ir turinčio vaiką statusą, kurio pasiekimas buvo visiems suprantamas ir nulemtas nusistovėjusio normatyvinio, linijinio gyvenimo kelio modelio, kuriame buvo aiškūs žingsniai, ką po ko daryti. Dėl to, kad jaunimas ilgiau dalyvauja švietimo sistemoje, vėliau įsilieja į darbo rinką, XX a. antroje pusėje pirmiausia Vakarų Europos šalyse pradėti fiksuoti linijiniam gyvenimo keliui nebūdingi bruožai: mažėja santuokų skaičius, šei-mos kuriamos vėliau, pirmieji vaikai gimsta vėlesniame amžiuje, vis dažniau pasirenkama savanoriška bevaikystė, didėja nesantuokinių vaikų skaičius, daugėja viengungių (Hutchison 2008;Vinken 2007;Stankūnienė, Jonkarytė, Mikulionienė, Mitrikas, Maslauskaitė 2003;Serdedakis, Tsiolis 2000 ir kt.).…”
Section: Jaunimo Apsirūpinimą Būstu Lemiantys Veiksniaiunclassified